2020
DOI: 10.20473/jaki.v8i1.2020.5-19
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Forming Breastfeeding Support Group Program to Improve Exclusive Breastfeeding

Abstract: Background: Exclusive breastfeeding is a problem of maternal and child health in Indonesia. With Breastfeeding Support Group, exclusive breastfeeding is expected to improve. Sugihwaras Village and Sumbergede Village have been initiating Breastfeeding Support Group program. However, the framework of Breastfeeding Support Group program and intervention methods for pregnant and breastfeeding mothers in both villages were different.Aim: It analyzed the effectiveness of forming Breastfeeding Support Group program a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The results from this study is in line with the previous study reported that weaning at 2 years of age is beneficial for the child, mom, and whole families [9][10][11][12]. Negative impact caused by early weaning, according to Quran expert, is not always considered as negative since breastfeeding practice needs consents and supports from both parents of the child and whole family [13][14][15]. It considers ability from the mother to breastfed and whole family to support.…”
Section: Development Of Weaning Indexsupporting
confidence: 89%
“…The results from this study is in line with the previous study reported that weaning at 2 years of age is beneficial for the child, mom, and whole families [9][10][11][12]. Negative impact caused by early weaning, according to Quran expert, is not always considered as negative since breastfeeding practice needs consents and supports from both parents of the child and whole family [13][14][15]. It considers ability from the mother to breastfed and whole family to support.…”
Section: Development Of Weaning Indexsupporting
confidence: 89%
“…programs. An article written byHasanah, Putri, and Pramono (2020) also pointed out similar results of the Breastfeeding Support Group Program. By comparing two different designs of program in the community, they showed the important factors that should be accommodated to sustain community empowerment programs on reproductive health.…”
mentioning
confidence: 72%
“…Studies have also shown that the support provided to breastfeeding mothers is an essential factor in successful breastfeeding in Indonesia [ 17 ]. However, studies on breastfeeding practices, the support provided during the COVID-19 pandemic, including the type of breastfeeding support (emotional, informational, instrumental and appraisal support), and the dominant support that affects the success of exclusive breastfeeding is still limited.…”
Section: Introductionmentioning
confidence: 99%